The N‐terminal pre‐A region of Mycobacterium tuberculosis 2/2HbN promotes NO‐dioxygenase activity. (16th November 2015) - Pesce, Alessandra; Bustamante, Juan P.; Bidon‐Chanal, Axel; Boechi, Leonardo; Estrin, Darío A.; Luque, Francisco Javier; Sebilo, Anne; Guertin, Michel; Bolognesi, Martino; Ascenzi, Paolo; Nardini, Marco
Abstract : A unique defense mechanisms by which Mycobacterium tuberculosis protects itself from nitrosative stress is based on the O2 ‐dependent NO‐dioxygenase (NOD) activity of truncated hemoglobin 2/2HbN ( Mt 2/2HbN). The NOD activity largely depends on the efficiency of ligand migration to the heme cavity through a two‐tunnel (long and short) system; recently, it was also correlated with the presence at the Mt 2/2HbN N‐terminus of a short pre‐A region, not conserved in most 2/2HbNs, whose deletion results in a drastic reduction of NO scavenging. In the present study, we report the crystal structure of Mt 2/2HbN‐ΔpreA, lacking the pre‐A region, at a resolution of 1.53 Å. We show that removal of the pre‐A region results in long range effects on the protein C‐terminus, promoting the assembly of a stable dimer, both in the crystals and in solution. In the Mt 2/2HbN‐ΔpreA dimer, access of heme ligands to the short tunnel is hindered. Molecular dynamics simulations show that the long tunnel branch is the only accessible pathway for O2 ‐ligand migration to/from the heme, and that the gating residue Phe(62)E15 partly restricts the diameter of the tunnel. Accordingly, kinetic measurements indicate that the k on value for peroxynitrite isomerization by Mt 2/2HbN‐ΔpreA‐Fe(III) is four‐fold lower relative to the full‐length protein, and that NO scavenging by Mt 2/2HbN‐ΔpreA‐Fe(II)‐O2 is reduced by 35‐fold. Therefore, we speculate that Mt 2/2HbN evolved to host the pre‐A region as a mechanism for preventing dimerization, thus reinforcing the survival of the microorganism against the reactive nitrosative stress in macrophages. Database: Coordinates and structure factors have been deposited in the Protein Data Bank under accession number5AB8 . Abstract : Removal of the pre‐A region in M. tuberculosis 2/2HbN ( Mt 2/2HbN‐ΔpreA) results in dimerization and in a reduced access to the heme pocket. Kinetic measurements indicate a 4‐fold decrease in k on for peroxynitrite isomerization and a 35‐fold decrease in NO‐scavenging relative to full‐length Mt 2/2HbN. Thus, the pre‐A region might be involved in reinforcing survival of the microorganism against nitrosative stress in macrophages.